Karakterisasi Ampermeter Voltmeter Terhadap Penambahan Hambatan pada Pengujian Sensor Mekanik Multimeter Analog - Suari, Muharmen (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
An analog multimeter mechanical sensor test has been conducted on the design of the ampermeter and voltmeter.Research background of the multimeter damage found in the measuring electronic circuit has burned some of its components but did not experience damage to the mechanical sensor.The research objective is to find out how to predict the voltmeter ampermeter measurement based on the addition of resistance to the analog multimeter mechanical sensor.Based on testing Â was found that the amount of electric current that can be passed by the sensor is 163.84uA and the resistance in the sensor is around 1 Kohm.When the sensor is used as a voltmeter by adding Rm in series, it can be determined the voltmeter measurement with the equation 0.1849Rm + 0.1988 (V) with an error of 1.16%.However, when the sensor is paralleled with a resistor, the ampermeter measurement can be determined by the equation 198.81 / Rs + 0.1638 with an error of 0.39%.Large resistance in the meter sensor is not the same there is a difference of 138.56 ohms.